2009
DOI: 10.1111/j.1365-2516.2008.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis in the haemophilia patient: a practical approach to care

Abstract: The major focus of care for patients with haemophilia is to ensure health with minimal joint dysfunction. As this population ages, additional coexisting conditions can develop including rare instances of nephrotic syndrome in haemophilia B inhibitor patients undergoing immune tolerance, hypertension, diabetes, and coronary artery disease, all of which can adversely affect the renal system over time. In haemophilia patients, co-infected with HIV and hepatitis C, these conditions can also increase the risk of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Previous research has indicated that risk factors for renal failure among individuals with hemophilia include increased age, hypertension, and HIV co-infection [1, 32]. Approximately 8% of patients in this sample had chronic renal disease, 20% of which also had HIV, and 40% of which had hypertension.…”
Section: Discussionmentioning
confidence: 78%
“…Previous research has indicated that risk factors for renal failure among individuals with hemophilia include increased age, hypertension, and HIV co-infection [1, 32]. Approximately 8% of patients in this sample had chronic renal disease, 20% of which also had HIV, and 40% of which had hypertension.…”
Section: Discussionmentioning
confidence: 78%
“…The general principle for RRT prescription is to treat patients with haemophilia like their age peers without haemophilia. Replacement therapy must be adapted to the baseline plasma factor deficiency and the risk of bleeding carried out by therapeutic procedures and eventually antithrombotic drugs (50). Actually, PD does not require specific prescriptions, as it does not need clotting factor replacement in relation with dialysis procedures.…”
Section: Rrt Prescriptionmentioning
confidence: 99%
“…Finally, the increased risk of renal problems in elderly haemophiliacs may result in the need for dialysis. Lambing et al (2009) recently reviewed the existing literature on dialysis in haemophilia patients. Haemodialysis, through an arterio‐venous fistula or central venous catheter and peritoneal dialysis are the treatment modalities applicable to persons with haemophilia.…”
Section: Clinical Management Of Co‐morbidities In Elderly Haemophiliamentioning
confidence: 99%